TRANSFER KEBIJAKAN DALAM JAMINAN KEHILANGAN PEKERJAAN DI INDONESIA - Nugroho Habibi (Halu Oleo University, 2025)
Policy transfer is the process of understanding policies, administration, institutions and ideas from other countries to be used in a policy. This study focuses on policy transfer in the JKP program, which is part of the National Social Security, in terms of form, approach and learning process. The method used in this study is descriptive qualitative which aims to provide an overview of the current conditions of JKP policy transfer. The study results show that the policy transfer in the JKP program can be implemented optimally even though the level of participation is still not proportional to the number of workers who are victims of layoffs. Productive-age beneficiaries also need to be given more attention so that they can contribute again to the world of work. Therefore, the government needs to develop JKP by conducting regular monitoring and evaluation so that it can reach a wider range of participants, see the level of re-employment and develop programs to target PKWT. This step is expected to provide more equitable and effective benefits for all workers who need the JKP program.